Savage, D. (2019) Non-Religious Pastoral Care, A Practical Guide. (25th February 2021) - Morgan, Geoff
Abstract : Savage, D. (2019) Non-Religious Pastoral Care, A Practical Guide. London and New York: Routledge, Taylor and Francis Group, 170 pp, (hbk) ISBN: 978-1-138- 57839-5.